Service Management Strategy of the Tirta Mayang Regional Water Company in Jambi City - Prayatna Lubis, Ade; Syarifuddin, Hutwan; Nazarudin, Nazarudin (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Climate change places significant pressure on the sustainability of clean water services, especially in areas that rely on a single source of raw water. Objective: This study aims to analyze the service conditions of Perumdam Tirta Mayang, Jambi City based on customer perceptions, identify internal and external factors that influence service sustainability, and formulate adaptive management strategies in dealing with the impacts of climate change. Methods: The research used quantitative and qualitative descriptive methods through field observations, in-depth interviews, and distribution of questionnaires to 100 active customers in 11 sub-districts in the service area, which were analyzed using SWOT analysis and IFAS and EFAS matrices. Results and Discussion: The level of customer satisfaction is in the good category. However, challenges still arise in the form of dependence on the Batanghari River as the sole source of raw water, decreased water pressure during the dry season, and increased turbidity during the rainy season. The SWOT analysis resulted in a strength score of 3.50 and a weakness score of 1.79 for internal factors, as well as an opportunity score of 3.48 and a threat score of 1.71 for external factors, which places perumdam tirta mayang in quadrant I. Conclusion: Recommended priority strategies include accelerating the construction of new intakes and WTPs to diversify raw water sources, optimizing the use of digital technology in processing and distribution systems, gradually improving the piping network, and strengthening cross-sector collaboration, including with the government, universities, and community organizations